2018
DOI: 10.1016/j.jiph.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Japanese encephalitis SA 14-14-2 live attenuated vaccine among Indian children: Retrospective 1:4 matched case-control study

Abstract: We concluded that the single subcutaneous dose of SA 14-14-2 JE vaccine provided moderate effectiveness in Indian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
3
24
2
Order By: Relevance
“…Postmarketing surveillance by the Indian Council of Medical Research reported SCRs, 28 days postvaccination, to be 67.2% in JE-naive children alone and 73.9% overall. The vaccine effectiveness estimate is reported to be 43.8% (95% CI, 1.9–67.8) for a single dose of SA 14-14-2 [ 30 ]. Despite the vaccine being available for more than 12 years, numerous JE outbreaks were reported, affecting an increased proportion of adults and children [ 9 , 31–36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postmarketing surveillance by the Indian Council of Medical Research reported SCRs, 28 days postvaccination, to be 67.2% in JE-naive children alone and 73.9% overall. The vaccine effectiveness estimate is reported to be 43.8% (95% CI, 1.9–67.8) for a single dose of SA 14-14-2 [ 30 ]. Despite the vaccine being available for more than 12 years, numerous JE outbreaks were reported, affecting an increased proportion of adults and children [ 9 , 31–36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, infection or vaccination usually results in the generation of antibodies that cross-react with all JEV genotypes. Therefore, vaccines have been developed mainly against JEV genotype III with live attenuated or formalin-inactivated virus (e.g., IXARIO ® ), which induce long lasting immunity and are well tolerated by children and aged people [88,89,90,91,92,93,94,95]. Of note, JEV infection and vaccination may induce antibodies that are cross-reactive with other flaviviruses, including DENV [71,83,96,97].…”
Section: Immune Response and Vaccinementioning
confidence: 99%
“…The incidence of Japanese encephalitis has however decreased in the recent years due to successful vaccination programmes in the 181 endemic districts of India, including eastern UP, Bihar, and West Bengal. 19 More recently, many other viruses like the enterovirus, Chandipura virus, Nipah virus, Zika virus, dengue virus, Chikungunya virus etc., have emerged and have been implicated in the outbreaks of AES in the Indian subcontinent. 20…”
Section: Etiologymentioning
confidence: 99%